Does corruption impact firm innovation? Evidence from Portugal - Jorge Cerdeira; Diogo Lourenço (Economies, 2022)
This paper aims to analyze the impact of corruption on firm innovation in Portugal, using data from the World Bank Enterprise Surveys on 1062 firms for 2019. We employ regression analysis and instrumental variables techniques to account for endogeneity in the corruption variable. Our results show that corruption fosters innovation in Portugal, regardless of the dependent variable we use to measure innovation. We have also analyzed the effect of corruption on innovation in foreign and domestic firms. While corruption boosts innovation for domestic firms, we found that the effect is not statistically significant for foreign firms. Our conclusions are of interest to policymakers, as any measure intended to fight corruption should consider its impact on firm performance. As this article shows, such an impact need not be negative. Nevertheless, if mitigating the impact of corruption is still intended, our results indicate that measures promoting foreign direct investment could help achieve this.
Keywords: 330; corruption; innovation; firm performance; foreign firms; IV estimation